MBRS-13. MiR-1253 POTENTIATES CISPLATIN RESPONSE IN PEDIATRIC MEDULLOBLASTOMA BY REGULATING FERROPTOSIS. (4th December 2020) - Kanchan, Ranjana K; Perumal, Naveenkumar; Atri, Pranita; Venkata, Ramakanth Chirravuri; Thapa, Ishwor; Nasser, Mohd Wasim; Batra, Surinder K; Mahapatra, Sidharth
Abstract: Despite improvements in targeted therapies, few group 3 medulloblastoma patients survive long-term. Haploinsufficiency of 17p13.3 is a hallmark of these high-risk tumors; included within this locus is miR-1253, which has tumor suppressive properties in medulloblastoma. Therapeutic strategies capitalizing on the anti-neoplastic properties of miRNAs can provide promising adjuncts to chemotherapy. In this study, we explored the potentiation of miR-1253 on cisplatin cytotoxicity in group 3 MB. Overexpression of miR-1253 sensitized group 3 MB cell lines to cisplatin, leading to a pronounced downregulation in cell viability and induction of apoptosis. Cisplatin is reported as an inducer of both apoptosis and ferroptosis-mediated cancer cell death. In silico analysis revealed an upregulation of several ABC transporters in high-risk MB tumors. When compared to cell lines overexpressing miR-1253, the ABC transporter ABCB7, which regulates both apoptosis and ferroptosis, was revealed as a putative target of miR-1253 with poor survival that may facilitate its chemosensitizing effects by modulating mitochondrial ROS and HIF1α-driven NFκB signaling. We observed high expression of ABCB7 and GPX4, ferroptosis regulators, in MB patients with poor overall survival. MiR-1253 negatively regulated the expression of ABCB7 in Group 3 MB cell lines and induced cytoplasmic ROS and mitochondrial O2-, suggesting ROS-mediated induction of ferroptosis through regulation of ABCB7 and GPX4. Treatment with ROS and ferroptosis inhibitors rescued miR-1253 transfected cells treated with cisplatin. We conclude that miR-1253 induced ROS and potentiated the ferroptotic effects of cisplatin via targeting miR-1253/ABCB7/GPX4/mtROS axis.